An IL-17–dominant immune profile is shared across the major orphan forms of ichthyosis - Paller, Amy S.; Renert-Yuval, Yael; Suprun, Maria; Esaki, Hitokazu; Oliva, Margeaux; Huynh, Thy Nhat; Ungar, Benjamin; Kunjravia, Norma; Friedland, Rivka; Peng, Xiangyu; Zheng, Xiuzhong; Estrada, Yeriel D.; et al. (Journal of allergy and clinical immunology, 2017)
The ichthyoses are rare genetic disorders associated with generalized scaling, erythema, and epidermal barrier impairment. Pathogenesis-based therapy is largely lacking because the underlying molecular basis is poorly understood. We sought to characterize molecularly cutaneous inflammation and its correlation with clinical and barrier characteristics. We analyzed biopsy specimens from 21 genotyped patients with ichthyosis (congenital ichthyosiform erythroderma, n = 6; lamellar ichthyosis, n = 7; epidermolytic ichthyosis, n = 5; and Netherton syndrome, n = 3) using immunohistochemistry and RT-PCR and compared them with specimens from healthy control subjects, patients with atopic dermatitis (AD), and patients with psoriasis. Clinical measures included the Ichthyosis Area Severity Index (IASI), which integrates erythema (IASI-E) and scaling (IASI-S); transepidermal water loss; and pruritus. Ichthyosis samples showed increased epidermal hyperplasia (increased thickness and keratin 16 expression) and T-cell and dendritic cell infiltrates. Increases of general inflammatory (IL-2), innate (IL-1β), and some TH1/interferon (IFN-γ) markers in patients with ichthyosis were comparable with those in patients with psoriasis or AD. TNF-α levels in patients with ichthyosis were increased only in those with Netherton syndrome but were much lower than in patients with psoriasis and those with AD. Expression of TH2 cytokines (IL-13 and IL-31) was similar to that seen in control subjects. The striking induction of IL-17–related genes or markers synergistically induced by IL-17 and TNF-α (IL-17A/C, IL-19, CXCL1, PI3, CCL20, and IL36G; P < .05) in patients with ichthyosis was similar to that seen in patients with psoriasis. IASI and IASI-E scores strongly correlated with IL-17A (r = 0.74, P < .001) and IL-17/TNF–synergistic/additive gene expression. These markers also significantly correlated with transepidermal water loss, suggesting a link between the barrier defect and inflammation in patients with ichthyosis. Our data associate a shared TH17/IL-23 immune fingerprint with the major orphan forms of ichthyosis and raise the possibility of IL-17–targeting strategies.